Curriculum reform A literature review to support effective implementation - Gouëdard, Pierre (OECD Publishing, 2020)
Countries consider curriculum reform as an important and necessary measure to make schools enter the 21st century and respond to a fast-changing world. In recent years, many OECD countries have engaged in curriculum reform as a way to equip children with the knowledge, skills and competences needed for tomorrow. However, how to initiate such change in the most suitable and effective way remains somewhat challenging. In other words, there is a missing step between the intention, and the realisation of this curriculum renewal, crystallising what has been coined in the literature "the implementation gap". This paper analyses the curriculum reform literature through the lens of the OECD proposed implementation framework that promotes, among others, inclusive stakeholder engagement. Curriculum reform has indeed long been considered from a "top-down" perspective, but has progressively shifted towards a more "bottom-up" approach, emphasising the central role of teachers in the process. The analysis is enriched with successful practices and examples from different countries, and concludes with a specific resource for countries to make the lessons learned actionable through the planning of a coherent curriculum implementation strategy
Keywords: Education